Dynamic Routing for HTTP Adaptive VBR Video Streaming Based on software deﬁned networking - Pham Hong Thinh; Ho Van Phi (My University, 2022)
Dynamic Routing for HTTP Adaptive VBR Video Streaming Based on software deﬁned networking
Keywords: HTTP Adaptive Streaming; Định tuyến SDN; VBR Video